2015
DOI: 10.1007/s11739-015-1325-2
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle interventions in preventing new type 2 diabetes in Asian populations

Abstract: The aim of this study was to review current evidence on interventional studies aimed at the prevention of type 2 diabetes in Asian population with lifestyle interventions. Prevalence of type 2 diabetes sharply increased in most Asian countries during the last decades. This issue has now also relevant implication for Europe where different surveys are also consistently revealing an higher prevalence of type 2 diabetes and other and major CVD risk factors among subjects originating from Asian Countries than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…Five studies had an AMSTAR score of ≤7 and were therefore excluded from sensitivity analyses (see above) 2630 34 37 40…”
Section: Resultsmentioning
confidence: 99%
“…Five studies had an AMSTAR score of ≤7 and were therefore excluded from sensitivity analyses (see above) 2630 34 37 40…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in order to reduce the burden of the disease in patients with type 2 diabetes, measures should be taken to reduce drug costs in conjunction with the implementation of drug price reform policies in Hubei Province. Moreover, because diabetes is a metabolic disease, in addition to access to affordable medication, health education and lifestyle interventions are also very important, as many studies have shown [31, 32]. In this way, both LOS and hospital costs would decrease.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO consultation group indeed recommended a lower cut-off of BMI for Asian with respect to native European populations [35] and the identified diagnostic cut-off for overweight in Chinese was 24 kg/m 2 [36]. This information is important in the light of prevention because the different cut-off value for obesity have to be adopted by physicians who are facing the new patients [37]. The existence of a distinct cut-off value is also to be communicated within the Chinese community because the emulation of native population might lead migrants to increased risk.…”
Section: Discussionmentioning
confidence: 99%